Emotional intelligence and COVID-19 anxiety in adolescents in San Martín region - García Castillo, Luz García Castillo (2022)
To determine if there is a significant relationship between emotional intelligence and anxietydue to COVID-19 in adolescents from the San Martín region, 2022. Methodology: Non-experimental,cross-sectional and correlational design, the study sample was 350 adolescents of both sexes from 11to 18 years old. The instruments used were the complete BarOn Ice-NA Emotional Intelligence Inventoryadapted to the Peruvian context by Ugarriza and Pajares (2004) and the Coronavirus Anxiety Scale(CAS) translated into Spanish by Rulman (2020). Result: There is a statistically significant relationshipwith a negative direction between emotional intelligence and anxiety (r = -.109* p < 0.05), with theexception of the stress management dimension that maintains a positive relationship with anxiety andthe degree of significance is higher (r = .023, p > 0.05), likewise the intrapersonal dimension maintainsa highly significant positive relationship with anxiety (r= .280**, p < 0.05), while in the interpersonaldimension there is an inverse and highly significant relationship with anxiety ( r = -.183**, p < 0.05),also in the adaptability dimension there is an inverse and highly significant relationship with anxiety (r= -.160**, p < 0.05). Conclusion: The higher the level of Emotional Intelligence, the lower the anxietyscores due to COVID-19 in adolescents from the San Martín region, 2022.